What works? a review of the efficacy and effectiveness of nutrition interventions - Allen, Lindsay H.; Gillespie, Stuart (United Nations, 2001)
This work was carried out as part of the ADB-IFPRI Regional Technical Assistance Project on Nutrition Trends, Policies and Strategies in Asia and the Pacific. This review tracks the life cycle impacts of malnutrition in the developing world, highlighting the dynamics of cause and consequence, and then considers what can be done to break the cycle: first from an efficacy perspective, then with regard to large scale effectiveness. Various issues are covered, including discussion on micronutrient deficiencies -- Vitamin A, iodine, and anemia; ways to avert low birth weight; measures to and improve maternal nutrition, child growth, and cognitive development; comprehensive review of the efficacy and effectiveness of supplementation and fortification trials; impact of food-based approaches to improve maternal and child nutrition; recommendations on a core program of proven efficacy and effectiveness; and a level of investment in operations to improve evidence-based nutrition programming.